Incidence and Mortality of Sarcomas in Shanghai, China, During 2002–2014 - Bao Pingping; Zhou Yuhong; Lu Weiqi; Wu Chunxiao; Wang Chunfang; Sun Yuanjue; Zhang Chenping; Xiao Jianru; Lu Jiade; Kong Lin; Cai Zhengdong; Zhang Weibin; et al. (Frontiers in Oncology, 2019)
Background: Sarcomas are a heterogeneous group of rare but deadly malignant tumors. The aim of this study was to comprehensively describe the incidence and mortality of sarcomas in Shanghai during 2002–2014.Method: Data were from Shanghai Cancer Registry. All new cases diagnosed with sarcomas and all death records where the cause of death listed as sarcomas were included. The characteristics of sarcomas incidence and mortality were analyzed. Age-standardized rates (ASRs) were adjusted by the world standard population. The trends were assessed by Joinpoint analysis.Results: A total of 9,440 incident cases were identified. The ASR was 3.4/105 for all sarcomas combined. Incidence of sarcomas overall was similar in females (3.5/105) as in males (3.4/105). Except for sarcomas “Not Otherwise Specified” (NOS), the most common histological subtype was gastrointestinal stromal sarcoma (GISS) (14.8%), which was followed by fibrosarcoma (7.2%), lipoblastoma (6.7%), leiomyosarcomas (6.5%), and osteosarcoma (5.3%). Among those incident cases, 87.9% were located in soft tissue sarcomas (STS) and 12.1% in bone and joint (bone sarcomas). The ASRs for STS and bone sarcomas were 2.8/105 and 0.6/105, respectively. Incidence rates for all STS combined rose exponentially with age, while bone sarcomas had the highest incidence at age 0–19.There were 4,279 deaths during 2002–2014 with the ASR of 1.3/105. Age-adjusted mortality due to sarcomas was slightly higher in males (1.5/105) than females (1.2/105). Except for sarcomas NOS, leiomyosarcomas was the most common subtype, comprising 9.9% of deaths due to sarcomas, followed by lipoblastoma (6.4%) and osteosarcoma (6.3%). The ASRs of mortality for STS and bone sarcomas were 1.0/105 and 0.2/105, respectively.For both males and females, the age-standardized incidence for STS and bone sarcomas did not change meaningfully over the study period. In contrast, age-standardized STS mortality in females increased by 2.3% per year (95% CI: 0.3, 4.4%), but was unchanged in males. No meaningful trends in bone sarcomas mortality were observed for either males or females.Conclusion: This population-based study was the first report of epidemiology of sarcomas in Shanghai according to anatomic site and histologic type. The diversity and rarity of sarcomas suggested more detailed data are warranted.